Block copolymer
By introducing polyester units with specific structures into polylactic acid resin, the biodegradability, hydrolysis resistance and tensile properties are improved, and the shortcomings of existing polylactic acid resins in the environment are solved, and activated sludge and Excellent performance in compost.
Patent Information
- Application Number
- CN202380046571.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-14
- Publication Date
- 2025-01-10
AI Technical Summary
The existing polylactic acid resins are insufficient in the environment for biodegradability and hydrolysis resistance, and have poor tensile properties, which limit their use in a wider range of applications.
Developed a block copolymer consisting of polylactic acid units and polyester units with a specific structure, which contain aliphatic diols and aliphatic dicarboxylic acids, by adjusting the number average molecular weight and structural ratio of the polyester unit, Improve biodegradability, hydrolysis resistance and tensile properties.
Block copolymers with excellent biodegradability, hydrolysis resistance and tensile properties in activated sludge and compost are achieved, meeting higher environmental friendliness and application needs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a block copolymer having excellent biodegradability, hydrolysis resistance and tensile properties. Background Art
[0002] From the perspective of environmental protection, the development of bioplastics is in full swing. Polylactic acid, a bioplastic made from renewable resources such as corn produced by photosynthesis, is expected to be used in a wide range of fields.
[0003] However, it is well known that polylactic acid is more brittle than petroleum-based plastics, has poor viscosity, flexibility, impact resistance, and heat resistance, and is easily hydrolyzed. Therefore, the use of polylactic acid as a resin material is sometimes limited. As an attempt to improve the shortcomings of polylactic acid, for example, a technology involving a resin composition or a molded body thereof formed by copolymerizing a polyester having a specific carbon number monomer with polylactic acid has been studied (for example, see patent documents 1 to 3). In addition, a technology for a resin composition formed by copolymerizing an amorphous polyester having a specific weight-average molecular weight with polylactic acid (for example, see patent document 4) and a stereocomplex of polylactic acid has been studied (for example, see patent document 5).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 8-157577
[0007] Patent Document 2: Japanese Patent Application Publication No. 9-100344
[0008] Patent Document 3: Japanese Patent Application Publication No. 2003-268125
[0009] Patent Document 4: Japanese Patent Application Publication No. 2014-1261
[0010] Patent Document 5: Japanese Patent Application Publication No. 2011-153275 Summary of the invention
[0011] Problems to be solved by the invention
[0012] It can be inferred that the resin or resin composition containing polylactic acid described in Patent Documents 1 to 5 has a certain degree of biodegradability. Here, biodegradability refers to the property of being finally decomposed into water and carbon dioxide by organisms such as microorganisms, and it is well known that the resin containing polylactic acid exhibits biodegradability in compost. However, due to the increase in environmental awareness, it is required to exhibit biodegradability in a wider range.
[0013] In addition, in order to suppress the progress of aging degradation in the final product formed of the resin material, it is necessary to have hydrolysis resistance. Therefore, it is necessary for bioplastics to have both biodegradability and hydrolysis resistance depending on the application.
[0014] Furthermore, for example, Patent Document 4 studies tear strength as a mechanical property of a resin composition, but does not describe tensile properties. From the viewpoint of the versatility of a resin composition, a resin composition having excellent tensile properties is desired.
[0015] Therefore, an object of the present invention is to provide a block copolymer having excellent biodegradability in activated sludge and compost, hydrolysis resistance, and tensile properties.
[0016] Means for solving problems
[0017] As a result of intensive studies to solve the above-mentioned problems, the inventors of the present invention have conceived of the present invention described below and have found that the problems can be solved.
[0018] That is, the present invention is as described above as follows.
[0019] [1] A block copolymer,
[0020] It contains a block structural unit (A) mainly composed of a polylactic acid unit (a) and a block structural unit (B) mainly composed of a polyester unit (b).
[0021] The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), the aliphatic diol (b1) is an aliphatic diol having 4 or more carbon atoms and having an alkyl group as a branch chain, and the number average molecular weight of the block structural unit (B) is 30,000 or more and less than 200,000.
[0022] [2] The block copolymer according to [1], wherein:
[0023] The content of the block structural unit (A) is 5% by mass or more and 95% by mass or less relative to 100% by mass of the total of the block structural unit (A) and the block structural unit (B).
[0024] [3] The block copolymer according to [1] or [2], wherein the aliphatic dicarboxylic acid (b2) has 4 or more and 12 or less carbon atoms.
[0025] [4] The block copolymer according to any one of [1] to [3], wherein the aliphatic diol (b1) has 10 or less carbon atoms.
[0026] [5] The block copolymer according to any one of [1] to [4], wherein the side chain of the aliphatic diol (b1) is a methyl group.
[0027] [6] The block copolymer according to any one of [1] to [5] above, wherein the glass transition temperature is -80°C or higher and -15°C or lower.
[0028] [7] The block copolymer according to any one of [1] to [6], wherein the decomposition rate after 15 days in the biodegradability evaluation in composting in accordance with ISO 14855-2:2018 is 10% by mass or more.
[0029] [8] The block copolymer according to any one of [1] to [7], wherein
[0030] After dissolving the block copolymer in chloroform at a concentration of 10% by mass, the block copolymer was poured onto a glass plate to prepare a film with a thickness of 200 μm, and then cut out in a manner to make a weight of 0.15 g. The obtained test sample was immersed in 50 mL of ion exchange water at pH 7 and placed at 50° C. The number average molecular weight was measured at prescribed intervals, and the time when the number average molecular weight was less than 90% of the initial number average molecular weight was more than 50 hours.
[0031] [9] The block copolymer according to any one of [1] to [8] above, wherein the elongation at break is 60% or more.
[0032] Effects of the Invention
[0033] According to the present invention, a block copolymer having excellent biodegradability in activated sludge and compost, hydrolysis resistance, and tensile properties can be provided. DETAILED DESCRIPTION
[0034] Hereinafter, an example of an embodiment of the present invention will be described. However, the embodiment described below is an example for actualizing the technical idea of the present invention, and the present invention is not limited to the following description.
[0035] In addition, in this specification, although the preferred mode of the embodiment is shown, the mode obtained by combining two or more of the preferred modes is also a preferred mode. Regarding the items represented by numerical ranges, when there are multiple numerical ranges, their lower limits and upper limits can be selectively combined as a preferred mode.
[0036] In addition, in this specification, when there is a description of a numerical range of "XX to YY", it means "XX or more and YY or less".
[0037] In this specification, "-to-unit" (here "-to" means a polymer) means "a structural unit derived from -to-." For example, "polylactic acid unit" means "a structural unit derived from polylactic acid," and "polyester unit" means "a structural unit derived from polyester."
[0038] In this specification, the "main chain" of a polymer refers to the longest molecular chain in a polymer molecule unless otherwise specified. In addition, the "branch chain" refers to a molecular chain other than the main chain in a molecule.
[0039] The block copolymer of the present embodiment contains a block structural unit (A) mainly composed of a polylactic acid unit (a) and a block structural unit (B) mainly composed of a polyester unit (b), and the number average molecular weight of the block structural unit (B) is 30,000 or more and less than 200,000.
[0040] The inventors of the present invention have conducted various studies on treatment schemes for imparting a wide range of biodegradability, excellent hydrolysis resistance, and tensile properties to block copolymers. As a result, the inventors of the present invention have found that the inclusion of block structural units (A) and block structural units (B) is an effective treatment scheme for imparting biodegradability in compost or even activated sludge and achieving excellent hydrolysis resistance. In addition, it has been found that when the number average molecular weight of the block structural unit (B) is within a specific numerical range, the tensile properties are also excellent.
[0041] The polyester unit (b) is characterized by comprising units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), wherein the aliphatic diol (b1) is an aliphatic diol having 4 or more carbon atoms and having an alkyl group as a branch chain.
[0042] It is inferred from the above characteristics that the block structure unit (B) is easy to become an amorphous polymer, so when biodegradation is carried out, microorganisms can easily enter the polymer structure, and the wide range of biodegradability is excellent. In addition, it can be considered that the aliphatic diol (b1) has an alkyl group as a side chain, thereby improving the hydrolysis resistance. On the other hand, when the block structure unit (B) is not an amorphous polymer, it can be considered that it is difficult for microorganisms to enter the polymer structure, resulting in difficulty in biodegradation, and the effect of the present invention cannot be obtained. However, the block structure unit (B) is an amorphous polymer, which is only one factor affecting biodegradability and hydrolysis. This is because it can be considered that biodegradation and hydrolysis are carried out by various factors such as whether the composite microorganism recognizes the amorphous structure as food, whether the enzyme or microorganism is easy to approach, the steric hindrance of the main chain, the melting point, and the degree of crystallinity. Therefore, the effect of the present invention is not obtained as long as it is an amorphous polymer. In addition, the reason why both wide-range biodegradability and excellent hydrolysis resistance in an opposite relationship can be achieved by having the above-mentioned polyester unit (b) has not yet been determined.
[0043] [Block structural unit (A)]
[0044] 〈Polylactic acid unit (a)〉
[0045] The block structural unit (A) contains the polylactic acid unit (a) as a main component.
[0046] The “main component” refers to a unit having the highest content ratio among the units constituting the block structural unit (A). The “main component” is preferably a unit having the highest content ratio by mass percentage among the units constituting the block structural unit (A).
[0047] The content of the polylactic acid unit (a) in the block structural unit (A) is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, further preferably 90% by mass or more, and may be 100% by mass. In addition, the upper limit of the polylactic acid unit (a) contained in the block structural unit (A) is not limited, and is, for example, 100% by mass or less.
[0048] The polylactic acid constituting the polylactic acid unit (a) may be prepared by a direct condensation method of lactic acid or by a ring-opening polymerization method of lactide. As the lactic acid, for example, at least one selected from L-lactic acid, D-lactic acid, and DL-lactic acid may be used. As the lactide, for example, at least one selected from L-lactide, D-lactide, DL-lactide, and meso-lactide may be used.
[0049] In addition, polylactic acid can be poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid, or a stereocomplex polylactic acid obtained by mixing poly-L-lactic acid and poly-D-lactic acid. From the viewpoint of cost, availability of raw materials, and ease of handling of block copolymers, polylactic acid is preferably poly-L-lactic acid, poly-D-lactic acid, and poly-DL-lactic acid, and more preferably poly-L-lactic acid and poly-D-lactic acid.
[0050] On the other hand, from the viewpoints of the cost and complexity of synthesis and the processability of the block copolymer, the polylactic acid is preferably not a stereocomplex polylactic acid.
[0051] From the viewpoint of more excellent biodegradability and hydrolysis resistance, the block structural unit (A) preferably contains 70% by mass or more of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid, more preferably 80% by mass or more, and even more preferably 90% by mass or more. For example, a technical solution in which the block structural unit (A) is composed of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid, that is, structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid account for 100% by mass, is an example of a preferred embodiment.
[0052] <Units (a') other than the polylactic acid unit (a)>
[0053] The block structural unit (A) may or may not contain a unit (a') other than the polylactic acid unit (a).
[0054] The monomer constituting the unit (a′) is not particularly limited within a range not impairing the effects of the present invention.
[0055] The content of the unit (a′) in the block structural unit (A) is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, and further preferably 10% by mass or less.
[0056] <Number average molecular weight of block structural unit (A)>
[0057] The number average molecular weight of the block structural unit (A) is preferably 5,000 to 150,000, more preferably 10,000 to 100,000, and even more preferably 20,000 to 40,000. Within the above numerical range, more excellent hydrolysis resistance can be exhibited.
[0058] In addition, when a block copolymer has a plurality of block structural units (A), the number average molecular weight of the block structural unit (A) represents the total of all blocks.
[0059] The number average molecular weight of the block structural unit (A) can be determined from the number average molecular weight of the block copolymer described below and the mass content of the block structural unit (A).
[0060] The number average molecular weight of the block structural unit (A) can be changed by adjusting the polymerization conditions of the polylactic acid, for example.
[0061] [Block structural unit (B)]
[0062] The block structural unit (B) contains the polyester unit (b) as a main component.
[0063] The “main component” refers to a unit having the highest content ratio among the units constituting the block structural unit (B). The “main component” is preferably a unit having the highest content ratio by mass percentage among the units constituting the block structural unit (B).
[0064] The content of the polyester unit (b) in the block structural unit (B) is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, particularly preferably 90% by mass or more, and may be 100% by mass. In addition, the upper limit of the content of the polyester unit (b) contained in the block structural unit (B) is not limited, and is, for example, 100% by mass or less.
[0065] The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). Specifically, the polyester unit (b) contains units derived from a polyester obtained by reacting an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). The polyester unit (b) may contain units derived from monomers other than the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2), or may not contain them.
[0066] Monomers other than the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) are not particularly limited as long as the effects of the present invention are not impaired.
[0067] The total amount of the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) in the polyester unit (b) is preferably 90 mol % or more, more preferably 95 mol % or more, further preferably 99 mol % or more, and may be 100 mol %.
[0068] <Aliphatic diol (b1)>
[0069] The aliphatic diol (b1) is an aliphatic diol having 4 or more carbon atoms and having an alkyl group as a branch. The aliphatic diol has two hydroxyl groups. The aliphatic diol (b1) generally excludes geminal diols. It is preferred that the two hydroxyl groups of the aliphatic diol (b1) are primary hydrocarbon groups. "Primary hydrocarbon group" refers to a hydroxyl group bonded to a primary atom, preferably a hydroxyl group bonded to a primary carbon atom.
[0070] In addition, the above-mentioned "carbon number" is the carbon number of the aliphatic diol (b1) as a whole including the carbon number forming the above-mentioned alkyl group.
[0071] The “branch” of the aliphatic diol (b1) refers to a partial structure branched from the “main chain” of the aliphatic diol (b1), and preferably, the terminal thereof is not bonded to a hydroxyl group.
[0072] The "main chain" of the aliphatic diol (b1) preferably refers to a partial structure of a molecular chain consisting of a plurality of carbon atoms connecting the two primary hydroxyl groups in the molecule at both ends. Therefore, the two primary hydroxyl groups in the aliphatic diol (b1) are preferably located at both ends of the "main chain" in the aliphatic diol (b1). In other words, the aliphatic diol (b1) preferably has hydroxyl groups at both ends of the main chain. Thus, a block copolymer that is easy to react with a dicarboxylic acid, easy to manufacture a triblock copolymer, and has better biodegradability and hydrolysis resistance can be obtained.
[0073] If the carbon number of the aliphatic diol (b1) is 3 or less, the hydrolysis resistance may be deteriorated. From the viewpoint of better hydrolysis resistance, the carbon number of the aliphatic diol (b1) is preferably 5 or more, more preferably 6 or more.
[0074] Furthermore, from the viewpoint of biodegradability, the carbon number of the aliphatic diol (b1) is preferably 10 or less, and more preferably 9 or less.
[0075] The carbon number of the main chain of the aliphatic diol (b1) is related to the carbon number of the branch chain, but is preferably 2 or more, more preferably 3 or more, further preferably 4 or more, further preferably 5 or more, and is preferably 9 or less, more preferably 8 or less.
[0076] When the aliphatic diol (b1) does not have an alkyl group as a branch chain, the block structural unit (B) is likely to crystallize, and the hydrolysis resistance of the block structural unit (B) may be deteriorated, so that the block copolymer cannot exhibit wide-range biodegradability and excellent hydrolysis resistance.
[0077] In the aliphatic diol (b1), the number of branches is preferably 1 or 2, and more preferably 1. In addition, the branch is preferably at least one of a methyl group, an ethyl group, and a propyl group, more preferably at least one of a methyl group and an ethyl group, and further preferably a methyl group. In addition, when the aliphatic diol (b1) has a plurality of branches, each branch may be the same or different.
[0078] Examples of the aliphatic diol (b1) include 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 1,4-pentanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,5-pentanediol, 2,4-dimethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 1,5-hexanediol, 2-ethyl-1,6-hexanediol, 2-methyl-1,8-octanediol. The aliphatic diol (b1) is preferably at least one of 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol and 2,4-diethyl-1,5-pentanediol, and more preferably 3-methyl-1,5-pentanediol.
[0079] The aliphatic diol (b1) may be used alone or in combination of two or more.
[0080] <Aliphatic dicarboxylic acid (b2)>
[0081] The carbon number of the aliphatic dicarboxylic acid (b2) is not limited unless the effects of the present invention are impaired. On the other hand, from the viewpoint of hydrolysis resistance, the carbon number of the aliphatic dicarboxylic acid (b2) is preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more. In addition, from the viewpoint of biodegradability, the carbon number of the aliphatic dicarboxylic acid (b2) is preferably 12 or less, more preferably 10 or less, and even more preferably 8 or less.
[0082] Examples of the aliphatic dicarboxylic acid (b2) include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and decanedicarboxylic acid. Succinic acid, adipic acid, and sebacic acid are preferred, and adipic acid is more preferred.
[0083] The aliphatic dicarboxylic acid (b2) may be used alone or in combination of two or more.
[0084] <Preferred combination of aliphatic diol (b1) and aliphatic dicarboxylic acid (b2)>
[0085] From the viewpoint of being able to exhibit more excellent biodegradability, hydrolysis resistance, and tensile properties, the combination of 2-methyl-1,3-propanediol and succinic acid, the combination of 3-methyl-1,5-pentanediol and succinic acid, the combination of 2,4-diethyl-1,5-pentanediol and succinic acid, the combination of 2-methyl-1,3-propanediol and adipic acid, the combination of 3-methyl-1,5-pentanediol and adipic acid, and the combination of 2,4-diethyl-1,5-pentanediol and adipic acid are examples of preferred embodiments; the combination of 3-methyl-1,5-pentanediol and succinic acid, the combination of 2,4-diethyl-1,5-pentanediol and succinic acid, the combination of 3-methyl-1,5-pentanediol and adipic acid, and the combination of 2,4-diethyl-1,5-pentanediol and adipic acid are examples of more preferred embodiments; and the combination of 3-methyl-1,5-pentanediol and adipic acid is an example of a further preferred embodiment.
[0086] <Ratio of aliphatic diol (b1) to aliphatic dicarboxylic acid (b2)>
[0087] The charging molar ratio [aliphatic diol (b1) / aliphatic dicarboxylic acid (b2)] when reacting the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) is preferably 1.4 / 1 to 1 / 1.4, more preferably 1.2 / 1 to 1 / 1.2.
[0088] <Unit (b') other than polyester unit (b)>
[0089] The block structural unit (B) may or may not contain a unit (b') other than the polyester unit (b).
[0090] The monomer constituting the unit (b′) is not particularly limited within a range not impairing the effects of the present invention.
[0091] The content of the unit (b′) in the block structural unit (B) is preferably 50% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, further preferably 15% by mass or less, particularly preferably 10% by mass or less.
[0092] <Number average molecular weight of block structural unit (B)>
[0093] The number average molecular weight of the block structural unit (B) is 30,000 or more and less than 200,000.
[0094] When the number average molecular weight of the block structural unit (B) is less than 30,000, tensile properties deteriorate.
[0095] When the number average molecular weight of the block structural unit (B) is 200,000 or more, synthesis becomes difficult and there is a risk that the production cost will increase.
[0096] From the viewpoint of exhibiting more excellent tensile properties, the number average molecular weight of the block structural unit (B) is preferably 33,000 or more, and more preferably 36,000 or more. From the viewpoint of ease of synthesis, the number average molecular weight of the block structural unit (B) is preferably less than 180,000, more preferably less than 150,000, and further preferably less than 120,000, and may be 100,000 or less, or 70,000 or less.
[0097] The number average molecular weight of the block structural unit (B) can be determined by gel permeation chromatography (GPC), and specifically can be measured according to the method described in Examples. In addition, the number average molecular weight of the block structural unit (B) can also be determined from the number average molecular weight of the block copolymer described below and the mass content of the block structural unit (B).
[0098] The number average molecular weight of the block structural unit (B) can be changed by adjusting the polymerization conditions of the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2), for example.
[0099] [Structural unit ratio]
[0100] The content of the block structural unit (A) is preferably 5 mass % or more and 95 mass % or less relative to 100 mass % of the total of the block structural unit (A) and the block structural unit (B).
[0101] When the proportion of the block structural unit (A) is 5% by mass or more, the strength and handleability of the block copolymer tend to be more excellent. In addition, when the proportion of the block structural unit (A) is 95% by mass or less, the flexibility, impact resistance and biodegradability of the block copolymer tend to be excellent, and the tensile properties are more excellent.
[0102] From the viewpoint of strength and handling properties, the proportion of the block structural unit (A) is more preferably 10% by mass or more, and further preferably 15% by mass or more. In addition, from the viewpoint of biodegradability and tensile properties, the proportion of the block structural unit (A) is more preferably 80% by mass or less, further preferably 75% by mass or less, further preferably 70% by mass or less, and further preferably 60% by mass or less.
[0103] The proportion of the block structural units (A) can be determined by 1 The H-NMR can be obtained, and specifically, it can be measured by the method described in the Examples.
[0104] In addition, the total content of the block structural unit (A) and the block structural unit (B) in the block copolymer is preferably 90% by mass or more, more preferably 95% by mass or more, and may be 100% by mass. In addition, the upper limit of the total content of the block structural unit (A) and the block structural unit (B) in the block copolymer is not limited, for example, it is 100% by mass or less.
[0105] The block copolymer may or may not contain units other than the block structural unit (A) and the block structural unit (B).
[0106] Units other than the block structural unit (A) and the block structural unit (B) are not particularly limited as long as the effects of the present invention are not impaired.
[0107] The content of units other than the block structural unit (A) and the block structural unit (B) in the block copolymer is preferably 10% by mass or less, more preferably 5% by mass or less.
[0108] [Number average molecular weight of block copolymer]
[0109] The number average molecular weight of the block copolymer is not limited as long as the number average molecular weight of the block structural unit (B) is 30,000 or more and less than 200,000. The number average molecular weight of the block copolymer may be, for example, 35,000 or more, or 40,000 or more. From the viewpoint of tensile properties and hydrolysis resistance, the number average molecular weight of the block copolymer is preferably 45,000 or more, 50,000 or more, or 55,000 or more, more preferably more than 58,000, further more preferably 60,000 or more, 65,000 or more, 70,000 or more, 75,000 or more, or 80,000 or more or 81,000 or more.
[0110] From the viewpoint of processability and productivity, the number average molecular weight of the block copolymer is preferably 450,000 or less, more preferably 350,000 or less, further preferably 250,000 or less, further preferably 200,000 or less, further preferably 150,000 or less, and may be 110,000 or less or 100,000 or less.
[0111] The number average molecular weight of the block copolymer can be determined by gel permeation chromatography (GPC), and specifically, can be measured by the method described in Examples.
[0112] The number average molecular weight of the block copolymer can be adjusted by, for example, the number average molecular weight of the block structural unit (A), the number average molecular weight of the block structural unit (B), and the number of each block structural unit.
[0113] [Block copolymer bonding form]
[0114] The combination form of the block copolymer is preferably a triblock type and a diblock type, and more preferably a triblock type. The block copolymer may also be a mixture of a triblock type and a diblock type. Specifically, the combination form is preferably [block structural unit (A)]-[block structural unit (B)]-[block structural unit (A)].
[0115] 〈Glass transition temperature of block copolymer〉
[0116] The glass transition temperature of the block copolymer is preferably -80° C. to -15° C. Within the above numerical range, the flexibility and impact resistance of the block copolymer tend to be excellent.
[0117] From the viewpoint of low-temperature properties such as impact resistance at low temperatures, the glass transition temperature of the block copolymer is more preferably -20°C or lower, further preferably -25°C or lower, and may be -30°C or lower, -40°C or lower, or -50°C or lower.
[0118] The lower limit value of the glass transition temperature of the block copolymer is preferably as low as possible, and may be, for example, -75°C or higher, -70°C or higher, or -65°C.
[0119] The glass transition temperature of the block copolymer can be determined by scanning calorimetry, and specifically, can be measured by the method described in Examples.
[0120] (Elongation at break of block copolymer)
[0121] The elongation at break of the block copolymer is not particularly limited, but is preferably 60% or more, more preferably 100% or more, further preferably 150% or more, further preferably 300% or more, particularly preferably 500% or more, and most preferably 600% or more. The elongation at break can be measured, for example, by the method described in the Examples in accordance with JIS K7161-1:2014.
[0122] (Hydrolysis resistance of block copolymers)
[0123] The hydrolysis resistance of the block copolymer can be evaluated, for example, by the following examples: after being dissolved in chloroform at 10% by mass, it is poured on a glass plate to make a film with a thickness of 200 μm, and then the test sample cut out in a way that becomes 0.15g of weight is immersed in 50mL of ion exchange water of pH7, placed at 50°C, and the number average molecular weight is measured at a predetermined time interval, thereby measuring the time when the number average molecular weight is less than 90% of the initial number average molecular weight. Although the hydrolysis resistance of the block copolymer is not particularly limited, the time when the number average molecular weight is less than 90% of the initial number average molecular weight is preferably 50 hours or more, more preferably 100 hours or more, more preferably 150 hours or more, more preferably 200 hours or more, particularly preferably 250 hours or more, and most preferably more than 400 hours. If the hydrolysis resistance of the block copolymer is within the above range, it is possible to use the block copolymer to manufacture products with excellent long-term reliability of mechanical properties.
[0124] (Biodegradability of block copolymers in composting)
[0125] The biodegradability of the block copolymer in compost can be measured, for example, by the method described in the examples based on ISO14855-2:2018. Although there is no particular limitation on the biodegradability of the block copolymer in compost, the decomposition rate after 15 days is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more. If the biodegradability of the block copolymer in compost is within the above range, for example, a product with a small environmental load and excellent compost biodegradability can be manufactured using the block copolymer.
[0126] (Biodegradability of Block Copolymers in Activated Sludge)
[0127] The biodegradability of the block copolymer in the activated sludge can be measured, for example, by the method described in the examples based on the method based on ISO14851:2019. Although the biodegradability of the block copolymer in the activated sludge is not particularly limited, the decomposition rate after 90 days is preferably 5% by mass or more. If the biodegradability of the block copolymer in the activated sludge is within the above range, for example, the block copolymer can be used to manufacture a product with excellent biodegradability and low environmental load in a drainage treatment facility.
[0128] [Method for producing block copolymer]
[0129] The block copolymer can be produced by a known production method.
[0130] (1) A known method for producing a block copolymer may be, for example, a method in which a polyester constituting the polyester unit (b) is synthesized and the polyester is polymerized with lactide.
[0131] The polyester can be synthesized by a known method. For example, the polyester can be synthesized by reacting an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2) using an esterification catalyst (eg, tin octylate, tin chloride, tin oxide).
[0132] When the polyester and lactide are polymerized, a ring-opening polymerization catalyst (eg, tin octylate, tin chloride, tin oxide) is preferably used. Examples of the polymerization reaction include solution polymerization, melt polymerization, and interfacial polycondensation, and any known polymerization reaction conditions may be used.
[0133] (2) Alternatively, a known method for producing a block copolymer may be used, for example, a method in which polylactic acid constituting the polylactic acid unit (a) and a polyester constituting the polyester unit (b) are separately synthesized and the polylactic acid and the polyester are reacted.
[0134] Polylactic acid can be synthesized by a known method. For example, polylactic acid can be synthesized by reacting lactic acid by a direct condensation method or by reacting lactide by a ring-opening polymerization method.
[0135] When the polylactic acid and the polyester are polymerized, an esterification catalyst (eg, tin octylate, tin chloride, tin oxide) is preferably used. Examples of the polymerization reaction include solution polymerization, melt polymerization, and interfacial polycondensation, and any known polymerization reaction conditions can be used.
[0136] Example
[0137] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited thereto.
[0138] The compounds used in Examples and Comparative Examples are as follows.
[0139] 3-Methyl-1,5-pentanediol (manufactured by Kuraray Co., Ltd.)
[0140] Adipic acid (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0141] Tin octylate (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0142] Toluene (manufactured by Kishida Chemical Co., Ltd.)
[0143] L-Lactide (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0144] Methanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0145] 2,4-Diethyl-1,5-pentanediol (Tokyo Chemical Industry Co., Ltd.)
[0146] 2-Methyl-1,3-propanediol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0147] Succinic acid (Tokyo Chemical Industry Co., Ltd.)
[0148] 1,4-Butanediol (Tokyo Chemical Industry Co., Ltd.)
[0149] Propylene glycol (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0150] The physical properties of the block copolymers in Examples and Comparative Examples were measured or evaluated by the following methods.
[0151] (1) Number average molecular weight (Mn)
[0152] The number average molecular weight (Mn) of the block copolymer was determined by gel permeation chromatography (GPC) in terms of standard polystyrene. The Mn of the block structural unit (B) was determined from the Mn of the block copolymer and the mass content of the block structural unit (B).
[0153] 〈GPC measurement conditions〉
[0154] Device: GPC device "HLC-8220" manufactured by Tosoh Corporation
[0155] Separation column: Tosoh Corporation "TSKgel SuperMultiporeHZ-M (column diameter = 4.6 mm, column length = 15 cm)" (two columns connected in series)
[0156] Eluent: Tetrahydrofuran (THF)
[0157] Eluent flow rate: 0.35mL / min
[0158] Column temperature: 40°C
[0159] Detection method: Differential refractive index (RI)
[0160] Injection volume: 10 μL
[0161] Concentration: 1 mg / 1 mL (block copolymer / THF)
[0162] (2) Hardness ratio (mass %) (mass content of block structural unit (A) mainly composed of polylactic acid unit (a))
[0163] pass 1 The hardness ratio of the block copolymer was calculated by H-NMR. Based on the area ratio of the signal near 5.2 ppm from the polylactic acid unit and the signal near 0.9 ppm from the structural unit (B) with the polyester unit (b) as the main component in the obtained spectrum, the molar ratio of the block structural unit (A) to the block structural unit (B) was calculated. The mass ratio of the block structural unit (A) adjusted so that the total of the mass ratios was 100 was taken as the hardness ratio.
[0164] 〈 1 H-NMR measurement conditions
[0165] Equipment: Nuclear magnetic resonance equipment "JNM-ECX400" manufactured by JEOL Ltd.
[0166] Solvent: deuterated chloroform
[0167] Measuring temperature: 50℃
[0168] Cumulative times: 1024 times
[0169] Measurement conditions: Heating rate 10℃ / min
[0170] (3) Biodegradability (composting)
[0171] The biodegradability in composting was measured according to the method in accordance with ISО14855-2: 2018. A was evaluated as A if the decomposition rate after 15 days was 20% by mass or more, B if it was 10% by mass or more and less than 20% by mass, C if it was 5% by mass or more and less than 10% by mass, and D if it was less than 5% by mass.
[0172] (4) Biodegradability (activated sludge)
[0173] The biodegradability in activated sludge was measured according to a method in accordance with IS014851: 2019. If the decomposition rate after 90 days was 5% by mass or more, it was evaluated as A, and if it was less than 5% by mass, it was evaluated as B.
[0174] (5) Hydrolysis resistance (h)
[0175] After dissolving the block copolymer in chloroform at 10% by mass, the block copolymer was poured onto a glass plate to prepare a film with a thickness of 200 μm, and then cut out to a weight of 0.15 g to prepare a test sample. The obtained test sample was immersed in 50 mL of ion exchange water at pH 7, placed at 50° C., and the number average molecular weight was measured at a predetermined time interval (specifically, every 50 hours), and the time when the number average molecular weight was less than 90% of the initial number average molecular weight was measured based on the plotted approximate curve.
[0176] It should be noted that when the above-mentioned elapsed time exceeds 400 hours, it is indicated as “>400 hours” in Table 1-1 and Table 1-2.
[0177] (6) Elongation at break
[0178] Test pieces were prepared using the block copolymers obtained in Examples and Comparative Examples and measured in accordance with JIS K7161-1: 2014. The test pieces were 100 μm thick pressed sheets annealed at 110° C. for 3 hours and then punched into dumbbell-shaped No. 3 dies for use. The tensile speed was 5 mm / min.
[0179] (7) Glass transition temperature (℃)
[0180] The glass transition temperature of the block copolymer was measured by a differential scanning calorimeter according to the method described in JIS K7121:2012.
[0181] Equipment: Differential Scanning Calorimeter "DSC822" manufactured by Mettler Toledo Co., Ltd.
[0182] Measurement conditions: Heating rate 10℃ / min
[0183] [Example 1]
[0184] 3-methyl-1,5-pentanediol and adipic acid were injected into a flask equipped with an apparatus capable of distilling off the generated liquid and a vacuum pump in a molar ratio of 3-methyl-1,5-pentanediol / adipic acid = 1.1 / 1, and tin octylate was added so that the total weight of 3-methyl-1,5-pentanediol and adipic acid was 0.1% by mass, and the mixture was heated at 160°C for 3 hours and 220°C for 3 hours under a nitrogen atmosphere and normal pressure, and the reaction was carried out while distilling off water. Then, the pressure was reduced to 2,000 Pa and the mixture was reacted for 3 hours, and then the pressure was reduced to 80 Pa and the mixture was reacted while appropriately confirming the number average molecular weight until the number average molecular weight reached 36,000, thereby synthesizing a polymer composed of a structural unit (B') having a polyester unit as the main component. After the reaction was completed, the pressure was returned to normal pressure, the temperature was cooled to 80°C, toluene was added to dilute the solid content concentration to 40% by mass, and the toluene solution was added to methanol in an amount twice the total amount of the solution. The supernatant was discarded, and methanol in an amount equal to the amount of the toluene solution was added again for washing. The supernatant was discarded, and the recovered insoluble components were dried at 40°C in a vacuum dryer to remove the organic volatile components, thereby obtaining a polymer composed of a structural unit (B') mainly composed of a polyester unit. 1 H-NMR measurement confirmed that the structures of both terminals were mainly hydroxyl groups derived from 3-methyl-1,5-pentanediol.
[0185] Toluene was added again to the purified polymer composed of structural unit (B′) to dilute the polymer to a solid content of 28.5% by mass, and then the temperature was raised to 140° C. to distill off 10% by mass of the added toluene, thereby dehydrating the system.
[0186] The mixture was then cooled to 80°C, and a polymer composed of structural unit (B') and L-lactide were added at a mass ratio of polymer composed of structural unit (B') / L-lactide = 60 / 40, and the weight of toluene removed by distillation was further added to adjust the solid content concentration to 40% by mass. The mixture was then heated to 100°C, and 0.1% by mass of tin octylate was added relative to the polymer composed of structural unit (B'), and the mixture was reacted for 10 hours to obtain a toluene solution of a block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b).
[0187] Toluene is added to the solution to dilute the solid content to 30% by mass, and then the toluene solution is added to a methanol volume twice the total volume of the solution to precipitate the solid. The methanol in the supernatant is discarded, and an amount of methanol equal to the amount of the toluene solution added is added again for washing. The methanol is discarded, and the recovered solid is dried at 40°C in a vacuum dryer to remove the organic volatile components, thereby obtaining a block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b). The obtained block copolymer 1 H-NMR measurement confirmed that the peaks derived from the methylene groups adjacent to both ends of the hydroxyl groups in the polymer composed of the structural unit (B') disappeared, and a triblock structure composed of a structure of [block structural unit (A)]-[block structural unit (B)]-[block structural unit (A)] was mainly generated.
[0188] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer had good biodegradability, hydrolysis resistance, and elongation at break.
[0189] [Examples 2, 3]
[0190] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit was obtained in the same manner as in Example 1, except that the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0191] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer had good biodegradability, hydrolysis resistance, and elongation at break.
[0192] [Example 4]
[0193] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b) was obtained in the same manner as in Example 1, except that 2-methyl-1,3-propanediol was used instead of 3-methyl-1,5-pentanediol, succinic acid was used instead of adipic acid, the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0194] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer had good biodegradability, hydrolysis resistance, and elongation at break.
[0195] [Example 5]
[0196] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b) was obtained in the same manner as in Example 1, except that 2,4-diethyl-1,5-pentanediol was used instead of 3-methyl-1,5-pentanediol, the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0197] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer had good biodegradability, hydrolysis resistance, and elongation at break.
[0198] [Example 6]
[0199] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b) was obtained in the same manner as in Example 1, except that 2-methyl-1,3-propanediol was used instead of 3-methyl-1,5-pentanediol, the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0200] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer had good biodegradability, hydrolysis resistance, and elongation at break.
[0201] [Example 7]
[0202] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit was obtained in the same manner as in Example 1, except that the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0203] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer had good biodegradability, hydrolysis resistance, and elongation at break.
[0204] [Comparative Example 1]
[0205] At 200° C., 0.1% by mass of tin octylate relative to L-lactide was added and reacted until the number average molecular weight reached 100,000, thereby obtaining polylactic acid.
[0206] The obtained polylactic acid was subjected to measurement and evaluation of biodegradability in activated sludge and in compost, hydrolysis resistance, and elongation at break. The results are shown in Table 1-2.
[0207] The block copolymer obtained in Comparative Example 1 had low hydrolysis resistance and elongation at break, and poor biodegradability. This is considered to be because it did not have the structural unit (B) having a polyester unit as a main component.
[0208] [Comparative Example 2]
[0209] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit was obtained in the same manner as in Example 1, except that the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0210] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-2.
[0211] The block copolymer obtained in Comparative Example 2 had good biodegradability, but had a low elongation at break. This is considered to be because the number average molecular weight of the block structural unit (B) was not within an appropriate range.
[0212] [Comparative Example 3]
[0213] A polymer composed of a structural unit (B'') composed of a polyester unit as a main component was synthesized in the same manner as in Example 1 except that 1,4-butanediol was used instead of 3-methyl-1,5-pentanediol, succinic acid was used instead of adipic acid, and the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed of a polyester unit as a main component. L-lactide was added at 200° C. so that the mass ratio of the polymer composed of the structural unit (B'') / L-lactide was 30 / 70, and 0.1% by mass of tin octylate was added relative to the polymer composed of the structural unit (B'') to react. While the reaction was allowed to proceed, L-lactide was added at any time until the number average molecular weight reached 140,000, thereby obtaining a block copolymer composed of a block structural unit (A) composed of a polylactic acid unit (a) as a main component and a block structural unit composed of a polyester unit as a main component.
[0214] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-2.
[0215] The block copolymer obtained in Comparative Example 3 was low in biodegradability, hydrolysis resistance, and elongation at break. This is considered to be because the diol used as a raw material did not have an alkyl group as a branch chain.
[0216] [Comparative Example 4]
[0217] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit composed mainly of a polyester unit was obtained in the same manner as in Example 1, except that propylene glycol was used instead of 3-methyl-1,5-pentanediol, succinic acid was used instead of adipic acid, and the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit.
[0218] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-2.
[0219] The block copolymer obtained in Comparative Example 4 had low hydrolysis resistance. This is considered to be because the carbon number of the diol used as a raw material was less than 4.
[0220] [Comparative Example 5]
[0221] A block copolymer composed of a block structural unit (A) mainly composed of a polylactic acid unit (a) and a block structural unit (B) mainly composed of a polyester unit (b) was obtained by the method described in Biomacromolecules 2013, 14, 2154-2161, Table 1 run no. 1.
[0222] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-2.
[0223] The elongation at break of the block copolymer obtained in Comparative Example 5 was low. This is considered to be because the number average molecular weight of the structural unit (B) was small.
[0224] [Table 1-1]
[0225]
[0226] [Table 1-2]
[0227]
[0228] The compounds represented by the abbreviations in Table 1-1 and Table 1-2 are as follows.
[0229] PLLA: Poly L-lactic acid
[0230] MPD: 3-methyl-1,5-pentanediol
[0231] DEPD: 2,4-diethyl-1,5-pentanediol
[0232] MPDiol: 2-methyl-1,3-propanediol
[0233] BD: 1,4-Butanediol
[0234] PG: Propylene glycol
[0235] AA: Adipic acid
[0236] SA: Succinic acid
[0237] As shown in the examples, the block copolymer of the present embodiment containing a specific block structural unit (A) with a polylactic acid unit (a) as the main component and a block structural unit (B) with a polyester unit (b) as the main component exhibits good biodegradability, hydrolysis resistance and elongation at break. Furthermore, the glass transition temperature of the block copolymer is relatively low, which is a preferred embodiment of the present application, and its low temperature characteristics can also be expected depending on the application. Therefore, the industrial applicability of the block copolymer of the present embodiment is extremely high.
Claims
1. A block copolymer comprising a block structural unit A mainly composed of a polylactic acid unit a and a block structural unit B mainly composed of a polyester unit b, The polyester unit b contains units derived from an aliphatic diol b1 and an aliphatic dicarboxylic acid b2, wherein the aliphatic diol b1 is an aliphatic diol having 4 or more carbon atoms and containing an alkyl group as a branch chain. The number average molecular weight of the block structural unit B is 30,000 or more and less than 200,000.
2. The block copolymer according to claim 1, wherein The content of the block structural unit A is 5% by mass or more and 95% by mass or less relative to 100% by mass of the total of the block structural unit A and the block structural unit B.
3. The block copolymer according to claim 1 or 2, wherein The aliphatic dicarboxylic acid b2 has 4 or more and 12 or less carbon atoms.
4. The block copolymer according to any one of claims 1 to 3, wherein The aliphatic diol b1 has 10 or less carbon atoms.
5. The block copolymer according to any one of claims 1 to 4, wherein The side chain of the aliphatic diol b1 is a methyl group.
6. The block copolymer according to any one of claims 1 to 5, wherein The block copolymer has a glass transition temperature of -80°C or higher and -15°C or lower.
7. The block copolymer according to any one of claims 1 to 6, wherein The block copolymer has a decomposition rate of 10% by mass or more after 15 days in a biodegradability evaluation in composting in accordance with ISO 14855-2:2018.
8. The block copolymer according to any one of claims 1 to 7, wherein After dissolving the block copolymer in chloroform at a concentration of 10% by mass, the block copolymer was poured onto a glass plate to prepare a film with a thickness of 200 μm, and then cut out in a manner of weighing 0.15 g. The obtained test sample was immersed in 50 mL of ion exchange water at pH 7 and placed at 50° C. The number average molecular weight was measured at prescribed intervals, and the time for reaching a value less than 90% of the initial number average molecular weight was more than 50 hours.
9. The block copolymer according to any one of claims 1 to 8, wherein The elongation at break of the block copolymer is greater than 60%.
Citation Information
Patent Citations
Production of transparent lactic acid copolyester, and packaging material
JP1996157577A
Polyactic acid block copolymer composition, its production and its molded product
JP1997100344A
Transparent material for packaging
JP2003268125A
Polyester resin, resin composition and molded body using the same
JP2011153275A
Polylactic acid-based resin composition and film or sheet using the same
JP2014001261A